Pengembangan Multimedia Interaktif pada Pembelajaran Biologi untuk Meningkatkan Kemampuan Kognitif Siswa Kelas VII SMPLB Tunarungu - Rahmawati M, Sri (Biology Teaching and Learning, 2020)
Abstract. This research is a Research and Development (R & D) which aims to determine the validity, practicality and effectiveness of interactive multimedia that has been developed in the material characteristics of living things. The research and development model used in the development of interactive multimedia for students of class VII SMPLB-B, refers to the ADDIE development model developed by Dick and Carry. The five main stages of the ADDIE model are Analyze, Design, Development, Implementation and Evaluations. Based on the results of the analysis of interactive multimedia learning media data that has been developed has met the criteria valid with a validity value of 4.49, has met the practical criteria with practicality value 4.22 classified as high category, classified as effective with an increase in cognitive aspects of students based onÂ  N-Gain scores by 0., 40 which belongs to the medium category Keyworods: multimedia interactive, research and development, valid, practical, effective